A Cross-sectional Study: How is The Relationship Between Social Determinants of Family Dimensions and Stunted Toddlers? - Andrei Ramani; Riris Diana Rachmayanti; Nur Farida Kusumawati; Rian Diana; Ali Khomsan; Hadi Riyadi (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2025)
Background: In East Java, the prevalence of stunting in toddlers exceeds the national average of 32.8%, while in Sampang Regency it reaches 47.9%. Stunting poses a significant challenge by hindering economic growth, exacerbating poverty, and widening socio-economic disparities. The research aims to analyze the relationship between family characteristics and the incidence of stunting in toddlers in Sampang, Madura.Method: This quantitative study employed a cross-sectional design in Sampang Regency. A total of 384 toddlers and their mothers participated as the research sample. The research variables included parental characteristics, anthropometric measurements of maternal height, and maternal knowledge status. Statistical analysis was conducted using the Pearson correlation inference test.Result: The test results showed that family social status had no significant influence on stunting among toddlers. However, maternal height significantly influenced the incidence of stunting, with a P-value of 0.030. These findings highlight the importance of addressing maternal height as a determinant of toddler stunting. Thus, intervention needs to be given to adolescent girls to prevent toddler stunting. Such interventions could include health education programs focused on improving adolescent nutritional status to increase growth. Efforts should prioritize adolescent girls before menarche to optimize height development and reduce the future stunting risk of their offspring.